1965
DOI: 10.1021/ac60228a002
|View full text |Cite
|
Sign up to set email alerts
|

Reactor Neutron Activation Analysis by the Single Comparator Method.

Abstract: of spectra considered and thus eliminate impossible components. Another approach is to use a provision which forces any selected group of spectra-preferably the major components-to enter the regression at the beginning of the calculations and then allow the regression to find the remaining components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
3

Year Published

1969
1969
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(29 citation statements)
references
References 8 publications
2
24
0
3
Order By: Relevance
“…Therefore, Girardi's well-known single-comparator method [5] was made flexible with respect to the irradiation conditions by using a mŸ of two (or better, three) monitors thus allowing the in-situ determination of the thermal to epithermal neutron flux ratio. In fact, this was one of the developments leading later on to the k0-method [6].…”
Section: Radiochemical Naa Of Semiconductor-grade Siliconmentioning
confidence: 99%
“…Therefore, Girardi's well-known single-comparator method [5] was made flexible with respect to the irradiation conditions by using a mŸ of two (or better, three) monitors thus allowing the in-situ determination of the thermal to epithermal neutron flux ratio. In fact, this was one of the developments leading later on to the k0-method [6].…”
Section: Radiochemical Naa Of Semiconductor-grade Siliconmentioning
confidence: 99%
“…This produces a significant error in thermal neutron activation o values if the cadmium ratio is less than 50 (29,30). Girardi et al (31,32) have shown that the nuclear constants involved are usually sufficiently well known to allow many elements to be determined absolutely with an accuracy of less than 10 percent.…”
Section: Sf = 1 --(6) 2nmentioning
confidence: 99%
“…In suggesting a technique we assume that the radioisotope to be separated is formed by the (n,y) reaction and is one of the most frequently used or "analytical" ones [59] .…”
Section: G Inorganic Separatorsmentioning
confidence: 99%
“…The neutron flux monitors consisted of high purity cellulose [9] on which known amounts of the standard solutions had been dried or 100 microliter aliquots of dilute (10-6 g/ml- 10 51 Cr, 59 Fe, 60 Co, 65 Zn, 75 A third set of gamma-ray spectra of the sample and standards was obtained with the gamma-gamma coincidence multidimensional analyzer about 45 days after irradiation and from these, the parent elements of the observed radionuclides 46 Sc, 60 Co, 65 The computer method used in these studies has been adapted from a method developed by Inouye and Rasmussen [6] for the analysis of complex gamma-ray spectra. Figure 2 shows the spectrum recorded over a period of 10 hours on a 25 ml sample of dried calcined blood.…”
Section: Introductionmentioning
confidence: 99%